Introduction into the international research project “In search of a legal model of self-employment in Poland. A comparative analysis - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The purpose of the present article is to present to the readers the key concepts underlying the international research project funded by the National Science Centre and led by Prof. Tomasz Duraj titled “In Search of the Self-Employment Model in Poland. A Comparative Analysis”. The chief research task undertaken by the project participants is a complex legal analysis of self-employment – not only from the perspective of Polish regulations and case law, but also with regard to solutions existing in international and Union law as well as in selected European countries. The area of study covered such legal systems as those of the United Kingdom, Germany, Austria, Spain, France, Italy, Hungary, as well as Lithuania, Latvia, and Estonia. Most centrally, the results of the study will serve to develop an original legal model of self-employment in Poland, which will redefine the special status of the self-employed in an optimal way. The final result of the international research project are two twin studies to be published by Lodz University Press, one in Polish, in the form of a multi-author monograph, and the other in English, as two issues of the journal Acta Universitatis Lodziensis. Folia Iuridica. The present article demonstrates the scale, significance, and implications of self-employment as an atypical form of providing work, as well as the key scholarly objectives of the international research project and its importance for legal theory and practice. Next, the author discusses the concept and the plan of research work adopted in the project, the research methods applied, and the publication and popularization activities carried out by the project participants. The research undertaken under the project is innovative. This is because until now, no such large-scale study into the legal conditions of self-employment in Poland has been carried out. The final conclusions drawn in the research project make a significant contribution to the development of the theory of labour law and social security law, enriching the academic discourse in this area. An added value for Polish scholarly work is the organized study of foreign regulations on self-employment in selected European countries. Moreover, the de lege ferenda remarks prepared in the research project may be helpful to the Polish authorities in developing new legal solutions in the area of self-employment.